Analisis Pengelolan Aset Tetap Pada Kantor Camat Kecamatan Banyuasin II Kabupaten Banyuasin - Amanda, Nurulia Putri; Nurmala, Nurmala; Sudiyanto, Totok (Universitas PGRI Palembang, 2024)
ABSTRACT This study aims to analyze the management of fixed assets at the District Office of Banyuasin II District, Banyuasin Regency, especially in the recognition, measurement, valuation and disclosure of fixed assets. The population of this research is the Fixed Assets Management in the Banyuasin II District Head Office, Banyuasin Regency. This research method uses descriptive qualitative where the analysis process is by compiling and analyzing regional fixed asset management. The data used is secondary data that is already available and has been collected at the District Office of Banyuasin II District, Banyuasin Regency. The results of this study concluded that the management of fixed assets, especially in the recognition, measurement, valuation and disclosure of fixed assets at the Banyuasin II Subdistrict Head Office, Banyuasin Regency, was in accordance with the Statement of Government Accounting Standards (PSAP) Number 07 concerning Accounting for Fixed Assets which had been carried out optimally. Keywords: Disclosure, Measurement, Valuation, Recognition, Fixed Assets. ABSTRAK Penelitian ini bertujuan untuk menganalisis pengelolaan aset tetap pada Kantor Camat Kecamatan Banyuasin II Kabupaten Banyuasin khususnya dalam pengakuan, pengukuran, penilaian dan pengungkapan aset tetap. Populasi penelitian ini adalah Pengelolaan Aset Tetap yang ada diKantor Camat Kecamatan Banyuasin II Kabupaten Banyuasin. Metode penelitian ini menggunakan deskriptif kualitatif dimana proses analisa dengan cara menyusun dan menganalisa pengelolaan aset tetap daerah. Data yang digunakan yaitu data sekunder yang sudah tersedia dan telah dikumpulkan pada Kantor Camat Kecamatan Banyuasin II Kabupaten Banyuasin. Hasil penelitian ini menyimpulkan bahwa pengelolaan aset tetap khususnya dalam pengakuan, pengukuran, penilaian dan pengungkapan aset tetap pada Kantor Camat Kecamatan Banyuasin II Kabupaten Banyuasin sudah sesuai dengan Pernyataan Standar Akuntansi Pemerintah (PSAP) Nomor 07 tentang Akuntansi Aset Tetap telah terlaksanakan dengan optimal. Kata kunci: Pengungkapan, Pengukuran, Penilaian, Pengakuan, Aset Tetap.